Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3847/0004-637x/826/2/107
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Formamide and Related Organic Species in the Interstellar Medium via Chemical Dynamics Simulations

Abstract: We show, by means of direct dynamics simulations, how it is possible to define possible reactants and mechanisms leading to the formation of formamide in the interstellar medium. In particular, different ion-molecule reactions in the gas phase were considered: NH 3 OH + , NH 2 OH + 2 , H 2 COH + , and NH 4 + for the ions and NH 2 OH, H 2 CO, and NH 3 for the partner neutrals. These calculations were combined with high level ab initio calculations to investigate possible further evolution of the products observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 59 publications
3
33
0
Order By: Relevance
“…In recent work 19 we studied ion-molecule collisions for formation of protonated formamide in the gas phase at different levels of theory. The PM6-D method was chosen for the ion/molecule collision dynamics to study GlyH + synthesis for three reasons: (i) for NH 2 OH 2 + + H 2 CO it gives a fraction of the water loss pathway similar to the MP2 results and this reaction is similar to the glycine formation reaction we are interested in; (ii) it includes dispersion, which may be important for describing approach of the reactants, and thus the results may be better than PM6; and (iii) PM6-D is included in the MOPAC semi-empirical software, which is interfaced with VENUS in an optimized way such that the calculations are much faster than when using MSINDO.…”
Section: Benchmark Of Semiempirical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent work 19 we studied ion-molecule collisions for formation of protonated formamide in the gas phase at different levels of theory. The PM6-D method was chosen for the ion/molecule collision dynamics to study GlyH + synthesis for three reasons: (i) for NH 2 OH 2 + + H 2 CO it gives a fraction of the water loss pathway similar to the MP2 results and this reaction is similar to the glycine formation reaction we are interested in; (ii) it includes dispersion, which may be important for describing approach of the reactants, and thus the results may be better than PM6; and (iii) PM6-D is included in the MOPAC semi-empirical software, which is interfaced with VENUS in an optimized way such that the calculations are much faster than when using MSINDO.…”
Section: Benchmark Of Semiempirical Methodsmentioning
confidence: 99%
“…Recently, we have shown that semi-empirical methods can be an alternative way to qualitatively understand reaction dynamics, mainly in the field of unimolecular dissociation, 21,22,23,24,25,26 and also in the study of ion-molecule collision, where we found that MSINDO semi-empirical Hamiltonian gives results qualitatively in agreement with MP2. 19 Here we first tested a larger variety of semi-empirical Hamiltonians on the reaction responsible to formamide formation for which we have benchmark MP2 results and thus used the one performing better to study the ion-molecule collisions of reactions 1 and 2. Present results show that both tautomers are able to react and form ions with the mass of protonated glycine but with different structures.…”
Section: Introductionmentioning
confidence: 99%
“…Following this hypothesis, quantum chemistry calculations reported that while some possible mechanisms for the formation of formamide (Redondo et al 2014b) and glycine (Barrientos et al 2012) should be discarded due to high reaction barriers, others are possible, like the formation of acetamide through H 2 NCHO + CH + 5 reaction (Redondo et al 2014a) or formamide through a radical mechanism (Barone et al 2015). Ion-molecule collisions were suggested as a possible mechanism in both experimental (Geppert & Larsson 2013;Larsson et al 2012;Blagojevic et al 2003;Petrie & Bohme 2007;Snow et al 2007) and theoretical studies (Spezia et al 2016). In this case even reactions with (small) activation barriers are possible thanks to the transformation in the collision of some of the translational energy into internal energy.…”
Section: )mentioning
confidence: 99%
“…In particular, they adopted the γ value from the former and the α and β values from the latter, Several ion-molecule reactions have also been considered from a theoretical point of view. [134][135][136] In particular, reactions involving ionic or protonated forms of nitrogen com-…”
Section: The Chemistry Of Interstellar Formamide: Theorymentioning
confidence: 99%